Diversidade e densidade do zooplancton em um transecto na foz do rio Pará (PA) - RODRIGUES, Emanuela Herondina (2020)
The Northern coast of Brazil is a privileged region for presenting a large and complex river system. It operates the Amazon Continental Shelf which is under the influence of Pará and Amazonas rivers certainly is among the most complex stretches of the Brazilian coast. In it, we aimed to characterize the zooplankton populations in terms of diversity and density for better environmental understanding, during July 2013, in a transect with six stations perpendicular to the shoreline, delimited from the coast to the continental slope, classified in the following geographic coordinates: Point A1 (PA1) 0°12'34.8'' latitude S and 48°06'34.1'' longitude O; Point A2 (PA2) 1°02'17.1'' N latitude and 47°54'46.3'' longitude O; A3 point (PA3) 1°12'34.3'' latitude N 47°43'25.2'' and longitude O; Point A4 (PA4) 0°45'50.07'' latitude N and 47°07'18.6'' longitude O; Point A5 (PA5) 0°69'55.2'' latitude N and 46°49'53.3'' longitude O; and the A6 point (PA6) 102'46.4'' latitude N and 46°49'03.8'' longitude O. Samples were collected by surface trawling with zooplankton net with mesh of 200 uM, endowed with flowmeter. After harvesting the material was fixed with 4% neutral formalin. In the laboratory, the samples were weighed to obtain the wet weight, analyzed until more specific level and accounted for density values. Ten major groups were recorded: Foraminifera, Cnidaria, Mollusca, Annelida, Phoronida, Crustacea, Echinodermata, Chaetognatha, Chordata and Copepoda. The assembly of the latter group was characterized by major species: Acartia tonsa, Farranula gracilis, Parvocalanus crassirostris, Corycaeus dubius, Corycaeus giesbrechti. The diversity indices were rising to the midpoint, the PA3 station, which was its peak and returned to decrease the logo of the transect. The composition of the zooplankton was characterized by estuarine, coastal and oceanic species, and the equitable distribution of these species.